2007
DOI: 10.1111/j.1538-7836.2007.02389.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential localization of recombinant factor VIIa to platelets activated with a combination of thrombin and a glycoprotein VI receptor agonist

Abstract: To cite this article: Kjalke M, Kjellev S, Rojkjaer R. Preferential localization of recombinant factor VIIa to platelets activated with a combination of thrombin and a glycoprotein VI receptor agonist. J Thromb Haemost 2007; 5: 774-80.Summary. Background: Activation of platelets with a combination of collagen and thrombin generates a subpopulation of highly procoagulant ÔcoatedÕ platelets characterized by high surface expression of fibrinogen and other procoagulant proteins. Objectives: To analyze the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 29 publications
1
47
0
Order By: Relevance
“…Finally, in vitro studies have shown that recombinant FVIIa preferentially binds to procoagulant platelets (34,35), and similar preferential binding to COAT platelets has been described for vatreptacog alfa, a novel recombinant FVIIa variant (36). Taking these data into account, the individual level of COAT platelets might be an important component for explaining the difference in hemostatic response to these drugs.…”
Section: Discussionmentioning
confidence: 70%
“…Finally, in vitro studies have shown that recombinant FVIIa preferentially binds to procoagulant platelets (34,35), and similar preferential binding to COAT platelets has been described for vatreptacog alfa, a novel recombinant FVIIa variant (36). Taking these data into account, the individual level of COAT platelets might be an important component for explaining the difference in hemostatic response to these drugs.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, it is possible that rFVIIa enters the brain parenchyma as a result of the pathological BBB disruption secondary to trauma and directly exerts its neuroprotective effects via this mechanism. Alternatively, rFVIIa controls bleeding pharmacologically by enhancing thrombin generation on the surface of platelets adherent to the site of vascular injury (Kjalke et al, 2007). Thrombin has been demonstrated to be neurotoxic at high concentrations and neuroprotective at low concentrations (Figueroa et al, 1998;Gorbacheva et al, 2006;Gingrich and Traynelis, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Alternatively, rhFVIIa administration is hemostatic through an activated platelet-dependent but TF-independent mode of action. Specifically, the poor affinity of FVII for anionic phospholipid membranes 8 necessitates large doses of rhFVIIa for treatment to generate hemostatic amounts of FXa. 9,10 This mode of action is supported by the greater clinical efficacy of an analog of rhFVIIa with enhanced TF-independent activity and platelet-binding sites.…”
Section: Introductionmentioning
confidence: 99%